2015
DOI: 10.3928/23258160-20151008-04
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Choroidal Thickness and Ciliary Artery Blood Flow Velocity in Normal Subjects

Abstract: The results of this study suggested there is an inverse proportional relationship between the RI of the SPCA and the subfoveal CT. The data also suggested a correlation between a decrease in the CT and increased RI in the retrobulbar arteries. Therefore, lower choroidal blood flow may explain the thinner CT in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 34 publications
(23 reference statements)
1
18
0
Order By: Relevance
“…37,38 One consequence of our findings is that uncorrected presbyopia, which results in hyperopic retinal defocus at near, would be expected to cause choroidal thinning during sustained near tasks or while spending time in a near environment. Because choroidal thinning has been associated with reduced choroidal blood flow in healthy subjects, 18 our findings suggest that adults with uncorrected presbyopia who spend prolonged periods engaged in near work may experience reduced choroidal blood flow.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…37,38 One consequence of our findings is that uncorrected presbyopia, which results in hyperopic retinal defocus at near, would be expected to cause choroidal thinning during sustained near tasks or while spending time in a near environment. Because choroidal thinning has been associated with reduced choroidal blood flow in healthy subjects, 18 our findings suggest that adults with uncorrected presbyopia who spend prolonged periods engaged in near work may experience reduced choroidal blood flow.…”
Section: Discussionmentioning
confidence: 68%
“…The proposed physiological mechanisms by which the choroid might dynamically increase or decrease in thickness include contraction and relaxation of nonvascular smooth muscle, 13 fluid redistribution as a result of osmotic changes, 16 and changes in choroidal blood flow. 17 Choroidal thickness and choroidal blood flow are correlated in animals 17 and healthy humans, 18,19 with choroidal thinning associated with reduced blood flow. Moreover, the choroid is typically thinner than normal, with reduced choroidal blood flow in patients with AMD [20][21][22][23] and those with diabetic retinopathy (DR).…”
mentioning
confidence: 99%
“…CTh can be easily measured using inbuilt calipers on OCT imaging software, making it accessible in research and clinical settings. While the true correlation between CTh and in vivo choroidal function, such as choroidal blood flow, remains uncertain [5], CTh is the closest objective marker of choroidal health available with present imaging techniques, making it a topic of great interest in outer retinal health.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed physiological mechanisms of dynamic increase or decrease of choroidal thickness include contraction and relaxation of nonvascular smooth muscle, 24 uid redistribution caused by osmotic changes, 25 and changes of choroidal blood ow. 26,27 It is known that surgical trauma can lead to the release of prostaglandins in the aqueous humor, thus causing damage to the blood/aqueous barrier. Our study found that CTs became signi cantly thicker 2 hours after surgery, especially in the fovea.…”
Section: Discussionmentioning
confidence: 99%